Effects of intraoperative hypothermia on stress hormone response in surgical patients - Zeba, Snježana; Šurbatović, Maja; Marjanović, Sonja (Vojnosanitetski pregled, 2022)
Background/Aim. Surgical stress itself, as well as hypothermia induced by general anesthesia and low ambient temperature, activates stress hormone response with changes in catecholamines and counter-regulatory hormones. The aim of this study was to investigate the acute hormone stress response in patients who underwent major surgical procedures and the efficiency of external and internal warming methods in alleviating these changes. Methods. The study included a total of 60 patients who underwent major open abdominal surgical procedures and were randomly divided into 4 groups: control non-warmed (C), externally warmed using forced-air warming mattress (W), internally warmed using intravenous amino acids (A), and warmed with a combination of external and internal method (A+W). Esophageal temperature was used as a measure of core temperature. Concentrations of epinephrine, norepinephrine, cortisol, prolactin, and testosterone were measured. Blood samples for hormone measurement were obtained at two time points for catecholamines – 90 min before and 120 min after finishing the surgery, and at additional two-time points for cortisol, prolactin, and testosterone (24 and 48 hrs after surgery). Results. In the W and A+W groups, the temperatures did not significantly differ between time points but constantly decreased in the C and A groups, with a statistically significant difference between the anesthesia induction and the 120th min (35.61 ± 042 vs. 33.86 ± 0.71 °C; p < 0.000 and 35.81 ± 0.54 vs. 34.45 ± 0.41 °C; p < 0.000, respectively). Catecholamine concentrations in all groups showed a significant increase during surgery, with the highest values recorded in the non-warmed group (777.07 ± 800.08 after vs. 106.13 ± 89.63 pg/mL before surgery for epinephrine and 1,349.67 ± 984.16 vs. 580.53 ± 465.38 for norepinephrine, p < 0.000). Concentrations of cortisol and prolactin also showed a significant increase at the same time point, with a tendency to normalize after 48 hrs. On the contrary, testosterone concentrations showed a decrease after 120 min without normalization throughout the entire period of observation. Except for testosterone, changes in all stress hormones were attenuated in warmed groups compared to controls. Conclusions. Regarding both features of surgical stress investigated in this study (hypothermia and stress hormone response), the combination of endogenous amino acid-induced thermogenesis and external air warming mattress is most effective in its prevention.
Keywords: anesthesia, general; body temperature; hormones; hypothermia; intraoperative complications; stress, physiological; surgical procedures, operative.